Modeling high performance multilayer antireflection coatings for visible and infrared (3-5μm) substrates - Asghar, M.H.; Khan, M.B.; Naseem, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Multilayer antireflection coatings have been modeled in visible and IR (3-5μm) bands to reduce reflectance from glass, germanium (Ge), silicon (Si) and zinc selenide (ZnSe) substrates. The transmittance of bare glass substrate is around 95% whereas for Ge 64%, Si 70%, ZnSe 84%. Theses values are enhanced reasonably by the application of multilayers films. Starting from a single layer, the layers have been added systematically forming multilayer structures to reduce reflectance considerably with each increasing layer. The designed layers are optimized for their performance by varying their thickness and refractive indices. The analysis of these modals has shown that the proposed multilayer structures are very effective in reducing the reflectance for all the substrates in two spectra.